(3GdafGf eMeO agej(B- (3PGcQI GdhGf GdSchf GdeJMQcs (Iraq; Ministry of Culture, 2015)
Cultural Series no. 17
Title translation: Mohammad Fahmi- Memory of Colors, Serene and Dynamic. By Ra'ad Kareem Aziz
Arabic
Keywords: N4390-5098 Visual Arts. Exhibitions; Iraq